EFFECT OF NITROGEN, PHOSPHOROUS AND POTASSIUM LEVELS ON THE PRODUCTIVITY OF INDUSTRIAL POTATOES - K. G. Saaseea; N. J. K. Al-a’amry (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The experiment was conducted using Potato( Solanum tuberosum L.) at the eastern Radwaniyah at private field during fall season 2020/2021 and spring 2021 to study the effect of nitrogen levels to 350, 275, 200 kg N h-1 ( N1, N2, N3) and phosphorous to 100, 180, 360 kg P2O5 h-1 ( P1, P2, P3) and potassium to 100, 200, 300 kg K2O h-1 ( K1, K2, K3) to vegetative growth and yield of industrial potato, The seeds of the hybrid potato Sinora, Class A, were planted in the fall season on 15/9/2020 and Elite in the spring season on 31/1/2021. The experimental fertilizers were added in four batches and in proportions according to the stages of plant age, Factorial experiment with RCBD using three replications. The results showed that changing the levels of the elements used to N3, P3, K3 led to a significant increases in most traits of vegetative growth for both seasons, while the change of phosphorous and potassium levels to P2 and K3 had a significant effect on the quantitative and qualitative yield for both seasons. The N1P2K3 interaction gave the highest marketable tuber weight, marketable yield plant-1, total yield for the fall and spring seasons, and the highest percentage of dry matter in tubers in the fall season.